Penggunaan Media Komik Strip Terhadap Pembelajaran Menulis Teks Anekdot di SMK Muhammadiyah Kajen - Riskiyani, Eka Mei; Hardiyanto, Fahrudin Eko (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The study was intended to describe the use of a comic book strip to teach anecdoatic text writing in class X SMK Muhammadiyah Kajen school year 2023/2024. The study uses a qualitative type of descriptive research. The data sources in the study are secondary and primary data. Primary data in research include student interviews, and interviews with educators. Secondary data in the study are the educators module for class X anecdote text material, the vlue data acquired by educated participants, the comics generated by educated, and the documentation during the process. Data collection techniques in this study include direct observation, interviews, and documentation. Studies have shown that the use of comics to write anecdotal texts has been found to be 31 (83%) educated people who get excellent credit, and there are 6 (17%) educated peole who score well on the overall rate of learnes. The strip’s comic media can be an alternative or solution in the learning process that can arouse learner’s interest in learning and learning motivation.